Upaya Pemberdayaan Ekonomi Masyarakat Melalui Pelatihan Pengelolaan Wakaf Produktif Berbasis Kearifan Lokal - sri kamba; Nur Mohamad Kasim; Trubus Semiaji (Madani: Jurnal Pengabdian Ilmiah, 2023)
Abstract: Waqf is a Maliyah worship that has excellent potential to be developed. Waqf assets provide significant benefits from time to time. However, in practice, the collection of waqf assets has not run optimally. The target of the mentoring and training activities is the community, especially the nazirs. This activity aims to increase knowledge, understanding and ability about effective waqf governance. The method used was mentoring and training with an intensive approach involving 30 participants and the Ministry of Religion of Gorontalo Province as resource persons. The results of these community service activities show that the community's knowledge, understanding and ability, especially the nazirs, regarding managing productive waqf has increased. This was obtained from a questionnaire distributed widely to the public. In addition, partners' views on productive waqf are not limited to management procedures but also on using property waqf to develop the economic potential of the people of Botutonuo Village. This strategy was carried out to support the realization of the management and utilization of waqf based on local wisdom, which focuses on the culture/habits of the people of Botutonuo Village who like to make waqf. Keywords: Waqf; Economic Empowerment; Training; Local Wisdom.